2001
DOI: 10.1073/pnas.141015098
|View full text |Cite
|
Sign up to set email alerts
|

BDNF but not NT-4 is required for normal flexion reflex plasticity and function

Abstract: Neurotrophins can directly modulate the function of diverse types of central nervous system synapses. Brain-derived neurotrophic factor (BDNF) might be released by nociceptors onto spinal neurons and mediate central sensitization associated with chronic pain. We have studied the role of BDNF and neurotrophin-4 (NT-4), both ligands of the trkB tyrosine kinase receptor, in synaptic transmission and reflex plasticity in the mouse spinal cord. We used an in vitro spinal cord preparation to measure monosynaptic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
2
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 41 publications
4
48
2
1
Order By: Relevance
“…Noxious thermal, mechanical, and chemical (capsaicin, mustard oil) stimuli induce phosphorylation of TrkB receptors in the SDH (Pezet et al, 2002), and application of the pan-Trk inhibitor, K252a, attenuates capsaicin-induced ERK phosphorylation in the SDH (Kawasaki et al, 2004), suggesting a role of endogenous BDNF in acute pain. Indeed, the nociceptive reflex is impaired from BDNF-deficient mice (Heppenstall and Lewin, 2001;MacQueen et al, 2001). However, sequestering endogenous BDNF with a TrkB-Fc fusion protein did not affect capsaicin-induced mechanical hypersensitivity in rats (Mannion et al, 1999).…”
Section: Functional Effects Of Bdnf On Pain-signaling Pathwaysmentioning
confidence: 96%
“…Noxious thermal, mechanical, and chemical (capsaicin, mustard oil) stimuli induce phosphorylation of TrkB receptors in the SDH (Pezet et al, 2002), and application of the pan-Trk inhibitor, K252a, attenuates capsaicin-induced ERK phosphorylation in the SDH (Kawasaki et al, 2004), suggesting a role of endogenous BDNF in acute pain. Indeed, the nociceptive reflex is impaired from BDNF-deficient mice (Heppenstall and Lewin, 2001;MacQueen et al, 2001). However, sequestering endogenous BDNF with a TrkB-Fc fusion protein did not affect capsaicin-induced mechanical hypersensitivity in rats (Mannion et al, 1999).…”
Section: Functional Effects Of Bdnf On Pain-signaling Pathwaysmentioning
confidence: 96%
“…The effects of mature BDNF on spinal synapses is rapid and probably occurs via both pre-and post-synaptic trkB receptors and the potentiation observed is because of phosphorylation of NMDA receptor subunits Heppenstall and Lewin, 2001;Garraway et al, 2003) (Figure 2). …”
Section: Mechanisms Of Ngf-dependent Mechanical Hyperalgesiamentioning
confidence: 99%
“…Nevertheless, studies using isolated spinal cords from young neurotrophin gene mutant mice have shown that the plasticity of ventral root potentials, which reflects C-fiber drive flexion reflexes, are selectively attenuated in the absence of BDNF, but not in the absence of NT-4 (Heppenstall and Lewin, 2001). A systematic examination of painrelated behaviors in BDNF heterozygote mutant mice also indicated that even reduced gene dosage of this important factor can lead to deficits in acute noxious heat sensitivity and reduced pain behaviors e.g.…”
Section: Mechanisms Of Ngf-dependent Mechanical Hyperalgesiamentioning
confidence: 99%
“…Unlike BDNF, NT-4 has no effect on activity-dependent synaptic plasticity or neuropathic pain (Heppenstall and Lewin, 2001;Yajima et al, 2002). To determine whether potential neuromodulatory effects of BDNF contributed to mechanosensory recovery, we gave rats bolus intrathecal injections of either IgG or TrkB-Fc (2 g of protein) on days 9 and 10 after DRI.…”
Section: Trkb-fc Treatment Enhances Mechanosensory Recovery Independementioning
confidence: 99%